The Role of Spiritual Leadership in Strengthening the Religious Culture of Schools - Achmad Suprayitno (International Journal of Islamic Pedagogical Research, 2025)
The problem underlying this study is the need to strengthen religious culture in Islamic educational institutions, particularly at the elementary level, where character building and spiritual development must be internalized through systematic leadership strategies. This research aims to analyze the strategies implemented by the principal of MI Semen Pinggir in developing a comprehensive religious culture based on the framework of Louis W. Fry’s Spiritual Leadership Theory. Using a qualitative descriptive method, data were collected through observations, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings show that the principal employs five main strategies: daily religious habituation, integration of Islamic values across academic and non-academic activities, implementation of special religious programs, reinforcement of teacher exemplary roles, and a humanistic leadership approach. These strategies align with the components of spiritual leadership, namely vision, altruistic love, and hope or faith, which collectively foster intrinsic motivation and strengthen the spiritual climate of the school. The study concludes that spiritual-based leadership significantly contributes to shaping students’ character and creating a cohesive Islamic environment. The implication is that principals should adopt spiritual leadership principles to enhance the effectiveness of religious culture development in Islamic schools.